From PEF to PBF: What difference does the longer alkyl chain make a computational spectroscopy study of poly(butylene 2,5-furandicarboxylate) - Nolasco, Mariela M.; Rodrigues, Leonor C.; Araújo, Catarina F.; Coimbra, Mariana M.; Ribeiro-Claro, Paulo; Vaz, Pedro D.; Rudić, Svemir; Silvestre, Armando J. D.; Bouyahya, Chaima; Majdoub, Mustapha; Sousa, Andreia F. (Frontiers in Chemistry, 2022)
This work explores the conformational preferences and the structure-property correlations of poly(butylene 2,5-furandicarboxylate) (PBF), a longer chain analogue of the most well-known biobased polyester from the furan family, poly(ethylene 2,5-furandicarboxylate) (PEF). A thorough computational spectroscopic study–including infrared, Raman and inelastic neutron scattering spectroscopy, combined with discrete and periodic density functional theory calculations–allowed the identification of dominant structural motifs in the amorphous and crystalline regions. Discrete calculations and vibrational spectroscopy of semi-crystalline and amorphous samples strongly support the predominance of gauche, trans, gauche conformations of the butylene glycol fragment in both the crystalline and amorphous domains. In what concerns the furandicarboxylate fragment, amorphous domains are dominated by syn,syn conformations, while in the crystalline domains the anti,anti forms prevail. A possible crystalline structure–built from these conformational preferences and including a network of C-H···O hydrogen bond contacts—was optimized using periodic density functional theory. This proposed crystal structure avoids the unrealistic structural features of the previously proposed X-ray structure, provides an excellent description of the inelastic neutron scattering spectrum of the semi-crystalline form, and allows the correlation between microscopic structure and macroscopic properties of the polymer.